Astrid Labibah (Politeknik Kesehatan Kemenkes Bandung, 2022)
Background: oxytocin massage is performed to the woman after birth to assit the hormone oxytocin in exputating of breast milk, acceling the parasimpative nerve sending signals to the back of the brain to stimulate oxytocin to secrete breat milk. Action massage can affect the hormone prolactin, functioning as a stimulus for milk production in the woman during breastfeeding. This action can also relax the woman and smoke neural flow and breast tracks in both breast. Objective: to know whether oxytocin massage can accelerate the ejection of breast milk in postpartum woman. Methods: searching on pubmed, google scholar and cochrane. Research results: results from the experimental group found increased breast milk production count 8.923 (p = 0.000) and experiment group t count 18,886 (p = 0.000), 17.09 to 220.91 cc and acceleration of breast milk production expenditure 5,15 hours.